Opportunistic use of catecholamine neurotransmitters as siderophores to access iron by Pseudomonas aeruginosa. (14th January 2021) - Perraud, Quentin; Kuhn, Lauriane; Fritsch, Sarah; Graulier, Gwenaëlle; Gasser, Véronique; Normant, Vincent; Hammann, Philippe; Schalk, Isabelle J.
Summary: Iron is an essential nutrient for bacterial growth and the cause of a fierce battle between the pathogen and host during infection. Bacteria have developed several strategies to access iron from the host, the most common being the production of siderophores, small iron‐chelating molecules secreted into the bacterial environment. The opportunist pathogen Pseudomonas aeruginosa produces two siderophores, pyoverdine and pyochelin, and is also able to use a wide panoply of xenosiderophores, siderophores produced by other microorganisms. Here, we demonstrate that catecholamine neurotransmitters (dopamine, l ‐DOPA, epinephrine and norepinephrine) are able to chelate iron and efficiently bring iron into P . aeruginosa cells via TonB‐dependent transporters (TBDTs). Bacterial growth assays under strong iron‐restricted conditions and with numerous mutants showed that the TBDTs involved are PiuA and PirA. PiuA exhibited more pronounced specificity for dopamine uptake than for norepinephrine, epinephrine and l ‐DOPA, whereas PirA specificity appeared to be higher for l ‐DOPA and norepinephrine. Proteomic and qRT‐PCR approaches showed pirA transcription and expression to be induced in the presence of all four catecholamines. Finally, the oxidative properties of catecholamines enable them to reduce iron, and we observed ferrous iron uptake via the FeoABC system in the presence of l ‐DOPA.